Budgeting levers, strategic agility and the use of performance budgeting in 2011/12 - Hawkesworth, Ian (OECD Publishing, 2013)
Governments need to be able to quickly and flexibly reallocate resources from one priority to another. This article addresses this dimension of strategic agility in terms of managing the reallocation of resources in the public sector through the use of various budgetary tools. The focus is on recent fiscal consolidation efforts, the use of performance information and spending reviews, and automatic productivity cuts. This article draws on the OECD survey on performance and results that was conducted in 2011/12; the data are accurate as of November 2012